Diallel analysis for seed yield and related traits in an energy crop jatropha curcas - Aminul Islam, A.K.M.; Nurina Anuar,; Zahira Yaakob,; Jaharah A. Ghani,; Mohamad Osman, (Universiti Kebangsaan Malaysia, 2015)
Six parents (P1, P2, P3, P4, P5 and P6) half diallel population of Jatropha curcas were evaluated to determine the combining ability, genetic components of variance and heterosis for yield contributing traits. Diallel analysis showed that both additive and dominance gene action was responsible for the genetic regulation of all the traits under study. The cross combination P1 × P3 showed the highest positive specific combining ability for seed yield per plant. Combining ability results were also in close agreement with the findings of estimate of genetic components of variance. The seeds per fruit (89%) and 100-seed weight (93%) showed maximum narrow sense heritability. Seed yield per plant showed high mid parent (254.13%) and better parent (202.36%) heterosis in the cross combinations of P2 × P5 and P1 × P3, respectively. The parents of P1, P2, P3 and P5 were found to be superior for seed yield components when used in cross. Considering seed production for each plant, the hybrids P1 × P2, P1 × P3, P2 × P5 and P4 × P6 could be selected for the development of hybrid varieties.